Pérdidas-duelos afectivos y su incidencia en los estados emocionales de los niños y niñas de primer año de educación general básica de la escuela de educación básica fiscal “Vicente Rocafuerte” de la parroquia Lican, cantón Riobamba, provincia de Chimborazo, período lectivo 2013 – 2014 - Jurado Vallejo, María Verónica (2014)
This thesis is about "LOSS-DUELOS AFFECTIVE AND ITS IMPACT ON THE EMOTIONAL STATES OF CHILDREN FIRST YEAR OF GENERAL BASIC EDUCATION SCHOOL OF BASIC EDUCATION TAX" VICENTE ROCAFUERTE "THE PARISH Licán, CANTON Riobamba, PROVINCE CHIMBORAZO, LECTIVO PERIOD 2013 - 2014. "LAS, PERIOD 2012" was structured and development under the current regulation of the Academic Board at the National University of Loja. The general objective was: To analyze the loss - Duels Affective and its impact on the Emotional States children Freshman of General Basic Education Basic Education School Fiscal "Vicente Rocafuerte" the Licán parish, Riobamba canton, province Chimborazo. The methods used were: Scientist, Inductive, Deductive, Analytic-Synthetic, Model Statistical them that served effectively help to achieve the target set; Techniques and instruments used were applied to the representatives of children and Observation Form applied to every child Freshman Basic Education Basic Education School Fiscal "Vicente Rocafuerte" Licán parish of Inquiry Riobamba to establish the causes and types of losses - Duels Affective crossing children. Having completed the analysis of the results of the instruments used in the research I have come to the following conclusions: 100% of the representatives said that their son / daughter has suffered a loss - Duel Affective cause of death; 78% due to the loss of a family member or friend; 56% for the loss of a pet; 37% by the loss of a toy; 28% by changing schools. The emotional state of the children who are going through a loss-Duel Affective according Observation Form has applied is 35% Anxiety and Mistrust; Sadness 26%; Hostility 23%; Nervousness and Depression 19% and 16% Irritability.